The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1460-9568.1998.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

A minigene of neural agrin encoding the laminin‐binding and acetylcholine receptor‐aggregating domains is sufficient to induce postsynaptic differentiation in muscle fibres

Abstract: The extracellular matrix molecule agrin is both necessary and sufficient for inducing the formation of postsynaptic specializations at the neuromuscular junction (NMJ). At the mature NMJ, agrin is stably incorporated in synaptic basal lamina. The postsynapse-inducing activity of chick agrin, as assayed by its capability of causing aggregation of acetylcholine receptors (AChRs) on cultured muscle cells, maps to a 21 kDa, C-terminal domain. Binding of chick agrin to muscle basal lamina is mediated by the laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…We have previously shown that a miniaturized form of neural agrin (miniagrin) containing the 8-aa insert at the B/z site is sufficient to induce postsynapse-like structures when expressed in nonsynaptic regions of the adult soleus muscle (23). To further study this phenomenon, we generated several transgenic mouse lines expressing miniagrin derived from full-length chick or mouse agrin (see Fig.…”
Section: Transgenic Expression Of a Miniaturized Form Of Neural Agrin Inmentioning
confidence: 99%
“…We have previously shown that a miniaturized form of neural agrin (miniagrin) containing the 8-aa insert at the B/z site is sufficient to induce postsynapse-like structures when expressed in nonsynaptic regions of the adult soleus muscle (23). To further study this phenomenon, we generated several transgenic mouse lines expressing miniagrin derived from full-length chick or mouse agrin (see Fig.…”
Section: Transgenic Expression Of a Miniaturized Form Of Neural Agrin Inmentioning
confidence: 99%
“…Thus, agrin binding to the myotube surface seems largely driven by its binding to ␣-dystroglycan and this increases its efficacy of activating MuSK. Similarly, the LG3 B8 domain is much more efficient in inducing postsynaptic specializations in vivo if the NtA domain, which confers binding to laminins, is included (59). Thus, the capturing of agrin to the muscle surface by its binding to either basement membrane or to the plasma membrane appears to have an important auxiliary function for the induction of postsynaptic structures.…”
Section: Tablementioning
confidence: 99%
“…1b). NA has previously been shown to possess AChR clustering and NMJ assembly properties of full-length agrin, whereas nNA was found to substantially ameliorate the dystrophic muscle histology and phenotype, prolonging animal survival when overexpressed in the muscle of laminin ␣2-deficient mice (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…24), and type IV collagen. For this study we have used "minigene" versions of non-neural (nNA) and neural agrin (NA) that consist of the N-terminal (NtA) laminin-binding domain and the C-terminal LG domains that have been shown to possess biological activity (25,26) and that were chosen to simplify the analysis of domain contributions. We have also evaluated full-length perlecan and a protein consisting of the NtA domain fused to the LG domains of perlecan (NP).…”
mentioning
confidence: 99%